Population genetic structure of the endemic rosewoods Dalbergia cochinchinensis and D. oliveri at a regional scale reflects the Indochinese landscape and life‐history traits. Issue 1 (1st December 2017) - Hartvig, Ida; So, Thea; Changtragoon, Suchitra; Tran, Hoa Thi; Bouamanivong, Somsanith; Theilade, Ida; Kjær, Erik Dahl; Nielsen, Lene Rostgaard
Abstract: Indochina is a biodiversity hot spot and harbors a high number of endemic species, most of which are poorly studied. This study explores the genetic structure and reproductive system of the threatened endemic timber species Dalbergia cochinchinensis and Dalbergia oliveri using microsatellite data from populations across Indochina and relates it to landscape characteristics and life‐history traits. We found that the major water bodies in the region, Mekong and Tonle Sap, represented barriers to gene flow and that higher levels of genetic diversity were found in populations in the center of the distribution area, particularly in Cambodia. We suggest that this pattern is ancient, reflecting the demographic history of the species and possible location of refugia during earlier time periods with limited forest cover, which was supported by signs of old genetic bottlenecks. The D. oliveri populations had generally high levels of genetic diversity (mean H e  = 0.73), but also strong genetic differentiation among populations (global G ST  = 0.13), while D. cochinchinensis had a moderate level of genetic diversity (mean H e  = 0.55), and an even stronger level of differentiation (global G ST  = 0.25). These differences in genetic structure can be accounted for by a higher level of gene flow in D. oliveri due to a higher dispersal capacity, but also by the broader distribution area for D. oliveri, and the pioneer characteristics of D. cochinchinensis . This study represents the first detailed analysis of landscape genetics for tree species in Indochina, and the found patterns might be common for other species with similar ecology. Abstract : Indochina is a biodiversity hot spot and harbors a high number of endemic species, most of which are poorly studied. We studied the genetic structure and reproductive system of the threatened endemic timber species Dalbergia cochinchinensis and D. oliveri from populations across Indochina. Both species exhibited highly structured genetic diversity patterns which could be related to landscape effects and life‐history traits.